Prevalence of Metabolic Syndrome in Thai Children: A Cross-sectional Study - Rerksuppaphol, Lakkana (JCDR Research and Publications (P) Limited, 2014)
Background: Metabolic syndrome in children has become the focus of many research projects in recent years. The main goal of this study is to evaluate the prevalence of metabolic syndrome in Thai children and its correlation with overweight and obesity. Material and Methods: A cross-sectional study of 348 children enrolled in grade 1 to grade 9 was done in Ongkhaluck province in Thailand. Demographic and anthropometric data were gathered. Blood tests were also performed to check for blood glucose, total cholesterol, and triglycerides. Results: The overall prevalence of metabolic syndrome in our population was 4.0%. Metabolic syndrome was found in 0.7% of non-obese/non-overweight children and 17.6% of obese/overweight children. Participants with metabolic syndrome were found to be significantly older, heavier, and taller and to have higher parameters of adiposity when compared with those without metabolic syndrome. Obesity was significantly correlated with every criterion of diagnosis of metabolic syndrome except Impaired Fasting Glucose (IFG). Conclusion: Findings of this study suggest that the prevalence of metabolic syndrome in Thai children is consistent with other reports from across the world.